Book Review: Islamic Law in Circulation: Shāfiʿī Texts Across the Indian Ocean and the Mediterranean, by Mahmood Kooria, Cambridge University Press, 2021. 240 pp. ISBN: 9781108481461 - Muhammad Fauzinudin Faiz; Syuhood B. Kooria (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2025)
This article reviews Islamic Law in Circulation: Shāfiʿī Texts Across the Indian Ocean and the Mediterranean by Mahmood Kooria, which explores the transmission of Islamic legal texts within maritime networks across the Indian Ocean and the Mediterranean. Kooria introduces the concept of